The Strategic Project Leader - Ferraro, Jack (Ascent Audio, 2018)
As executives build and nurture their organization's strategic agility in today's turbulent, uncertain business environment, the ability to lead strategic change has become more critical than ever. The Strategic Project Leader: Mastering Service-Based Project Leadership, Second Edition will help project managers lead with confidence in temporary, ambiguous team structures that execute risk-laden work in an increasingly agile project environment. This book encourages listeners to take ownership of their leadership agenda and become disciplined in the processes of building a framework of leadership skills. Listeners are introduced to a new role: the service-based project leader. This role serves the entire project organization by creating a meaningful experience for team members, customers, and critical stakeholders. The book provides practical guidance to help you move from project manager to service-based project leader. Detailing a framework for developing and refining leadership skills, it explains how to build a leadership competency pyramid and then execute a self-directed plan for building leadership competencies. The leadership competency pyramid includes an intuitive model that will be helpful to project managers at any level. The book elaborates on the components of each layer of the pyramid and how each layer relates to the others. A chapter is dedicated to each layer of the pyramid, with supporting evidence for the necessity of each of these layers, as well as practical advice on how to build and practice these component layers.
Online resource; Title from title page (viewed December 12, 2018)
Keywords: Computers; Electronic digital computers; Ordinateurs; computers; Audiobooks